Determination of mycotoxins in beer by multi heart-cutting two-dimensional liquid chromatography tandem mass spectrometry method. (15th July 2020) - Campone, Luca; Rizzo, Serena; Piccinelli, Anna Lisa; Celano, Rita; Pagano, Imma; Russo, Mariateresa; Labra, Massimo; Rastrelli, Luca
Highlights: A multi heart-cutting 2D-LC method was developed and validated. Automated analysis of aflatoxins, ochratoxin A and fumonisins in beer was achieved. C8 and kinetex Biphenyl column was coupled in 1D and 2D dimension respectively. A significant decrease of matrix effect was achieved by 2D-chromatography. Fumonisins B1 and B2 were found in the analysed real samples. Abstract: Beer is one the most consumed alcoholic beverage in the world and its contamination with mycotoxins is of public health concern. This study reports a fast and automated analytical procedure based on a multi-heart-cutting two-dimensional liquid chromatography tandem mass spectrometry method using electrospray ionization for the determination of seven mycotoxins (aflatoxins B1, B2, G2 and G1, ochratoxin A, fumonisins B1 and B2) in beers. The developed method was based on the heart-cutting 2D- HPLC technique in which only the specific portions of the first dimension, in the retention time of analytes, were transferred into the second dimension for the further separation and successive determination. The method uses two different chromatographic columns; in the first dimension, 50 μL of sample was injected on first column, and mycotoxins elution regions were collected in a loop and transferred into the second column for the separation of analytes. Each column operated in gradient elution mode in order to eliminate interfering compounds and improve separation and peak shape. After the optimization, the method has been validated according to EU regulation and finally applied for the analysis of forty beer samples collected from Italian supermarkets. Among all mycotoxins studied, fumonisins B1 was the most widely distributed in analysed beers (>21%) in the range from 0.6 to 12.3 ng mL −1 . The automated methodology developed was able to determine accurately and simultaneously seven mycotoxins in beer. This provided a significant reduction of sample handle and, consequently of analysis time.